SPECIFIC ASPECTS OF PROFESSIONAL TRAINING DEVELOPMENT IN PROFESSIONAL EDUCATION - Samaridin Barakayevich Qorayev (Western European Studies, 2024)
This article analyzes the specific aspects of developing professional training in vocational schools. Emphasis is placed on the importance of practice-oriented curricula, the implementation of modern technologies, the preparation of qualified teachers, and the development of students' professional skills. The article also explores the adaptation of vocational education to labor market demands and social needs, along with challenges and solutions for preparing students for the workforce
Keywords: vocational school; professional training; practical education